Transformational Leadership And Organizational Climate As Determinants Of Knowledge Behaviour At A Tutoring Center In Malang City - Novi Kurnia; Vivin Maharani Ekowati (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the effects of transformational leadership on knowledge sharing and knowledge hiding, and to examine the mediating role of organizational climate in tutoring institutions in Malang City. This research employed a quantitative research design with a survey method. Data were collected through questionnaires using a Likert scale and distributed to 78 tutors and staff members of tutoring institutions in Malang City, and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that transformational leadership has a positive and significant effect on knowledge sharing, but does not significantly affect knowledge hiding. Furthermore, organizational climate has a negative and significant effect on knowledge hiding. The mediation analysis indicates that organizational climate does not mediate the relationship between transformational leadership and knowledge sharing. The study highlights the importance of transformational leadership and a supportive organizational climate in promoting knowledge-sharing behavior and reducing knowleidgei hiding within non-formal eiducational organizations.